Antifungal Studies of Transition Metal Complexes of Schiff Base Derived from Anthracene Carboxaldehyde-L-Histidine - Indira Devi, G.; Parameswaran, Geetha; Veena, V. (Asian Journal of Chemistry, 2010)
Transition metal complexes with Schiff bases as ligands have been amongst the most widely studied coordination compounds. Schiff bases and their metal complexes have found a multitude of uses. Amino acid complexes have been attracted by the biochemists because of its vast application. The antifungal behaviour of the Schiff base anthracene carboxaldehyde L-histidine and its complexes with Cu(II), Co(II), Mn(II) and Ni(II) has been studied individually. The effects of the above mentioned complexes were tried on different growth phases of Phytophthora capsici, the casual organism of foot rot of black pepper (Piper nigrum. L.). The results showed that the antifungal activity of the above complexes depends on metal coordination and the concentration of the test solution used. Due to chelation, the percentage inhibition of these complexes increases.